Effect Of Brand Image And Product Quality On Purchase Decision Of Scarlett Whitening In Medan City - Sinaga, Mega Astria; Hafiza Adlina (Journal Arbitrase : Economy, Management and Accounting, 2023)
Scarlett Whitening is a new brand but is quickly becoming famous and selling well among the public amidst the intense competition in the Indonesian cosmetics industry which has given rise to many new cosmetic brands in recent years. This research aims to find out how brand image and product quality influence Scarlett Whitening product decisions in the city of Medan, both partially and simultaneously. The type of research used in this research is quantitative research with an associative approach. The sampling technique was purposive sampling, totaling 100 respondents. The data analysis techniques used are validity test, reliability test, classical assumption test, multiple linear regression test, T test, F test and coefficient of determination test. The research results show that brand image and product quality have a positive and significant effect on purchasing decisions for Scarlett Whitening products partially and simultaneously. The correlation coefficient value is 0.870, which indicates that there is a fairly strong correlation between the brand image variables and product quality on purchasing decisions. The R Square value of the purchasing decision variable of 75.7% can be explained by the brand image and product quality variables, while the remaining 24.3% is influenced by other variables not included in the research.